SITUS TRADISI BERLANJUT DI BUAHDUA SUMEDANG - Effie Latifundia; sudarti prijono (Kemendikbud, 2018)
The prehistoric tradition that still continues today is the megalithic tradition. Therefore the megalithic tradition is a system of sustainable cultural values or so-called traditions continue. Characteristic of megalithic tradition is ancestor worship or ancestral spirit. Until now, some villages in the area of Buahdua-Sumedang megalithic tradition still continues and can not even be separated from the life of the community supporters. The purpose of this study to explore the sites of tradition continues in the life of the people of Buahdua and surrounding areas even though Islam has grown and embraced. This research is conducted by survey method to collect information and describe the forms of cultural relation with megalithic tradition. The results show that although Islam has grown and adhered to, but the worship of ancestors as local religious understandings before Islam developed still continues. The form of simple ancient tombs with erect stone tombstone, petilasan / tread and even a collection of large stones irregular stone until now still visited for the worshiped or pilgrimage.Keywords: megalithic tradition, tomb, pilgrimage.